2023
DOI: 10.1021/acs.accounts.3c00009
|View full text |Cite
|
Sign up to set email alerts
|

Chalcogen Bonding Catalysis with Phosphonium Chalcogenide (PCH)

Abstract: Metrics & MoreArticle Recommendations CONSPECTUS:The exploration of new catalysis concepts and strategies to drive chemical reactions is of vital importance for the sustainable development of organic synthesis. Recently, chalcogen bonding catalysis has emerged as a new concept for organic synthesis and has been demonstrated to be an important synthetic tool capable of addressing elusive reactivity and selectivity issues. This Account describes our progress in the research field of chalcogen bonding catalysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…Under these circumstances, we expect a differentiation of the two σ-holes up to a point where the strongest one will essentially control the supramolecular organization of cocrystals, in a way similar to that observed with XB. As illustrated in Figure b, this approach has been already used in cationic ChB donors aimed at interacting with different neutral or anionic Lewis bases toward anion recognition effects or organo-catalysis applications. …”
Section: Directionality Control Through Chalcogen Dissymmetrizationmentioning
confidence: 99%
“…Under these circumstances, we expect a differentiation of the two σ-holes up to a point where the strongest one will essentially control the supramolecular organization of cocrystals, in a way similar to that observed with XB. As illustrated in Figure b, this approach has been already used in cationic ChB donors aimed at interacting with different neutral or anionic Lewis bases toward anion recognition effects or organo-catalysis applications. …”
Section: Directionality Control Through Chalcogen Dissymmetrizationmentioning
confidence: 99%
“…This heavy-atom effect is beneficial for phosphorescence. 56,57 It has also been found that halogen atoms endow an interesting ''halogen effect'' in tuning the selfassembling and functional properties, such as gelation, 58 mechanofluorochromism (MFC), 59 aggregation-induced emission (AIE), 60,61 room-temperature phosphorescence (RTP), thermally activated delayed fluorescence (TADF), [62][63][64] near-infrared fluorescence, 65 sensing, 66 supramolecular structures 67 and crystalline structures. 68 Considering that halogens can be used as a useful crystal engineering tool for topological chemical reactions, 69 the halogen effect plays a more indispensable role in fabricating photomechanical organic crystals.…”
Section: Ran Lumentioning
confidence: 99%
“…Differing from XB, each chalcogenide atom is capable of establishing two sigma holes, which could confer ChB catalysts unique activation manifolds inaccessible through XBs. In particular, a privileged class of phosphonochalcogenide catalysts [9] developed by Wang and co‐workers has gained significant attention lately owing to the robustness of this catalyst across different reaction classes (Figure 1B). To date, the predominant proposed mode of activation of such catalysts solely involved Lewis acidity through the sigma holes of the selenium atoms, [10] which can be harnessed to activate electrophiles, such as carbonyl motifs.…”
Section: Introductionmentioning
confidence: 99%